Optimasi Sistem Pengelolaan Sampah Terintegrasi Berbasis Lean Waste Management untuk Peningkatan Efisiensi dan Keberlanjutan Lingkungan di Kota Kudus - Kukuh Mukti Wibowo; intakoris, sam'ani; firmansyah, nunung agus; masithoh, anny rosiana; nadhifah, Tuti (Pusat riset dan Inovasi Nasional, 2025)
Waste management problems in Kudus City show high complexity, marked by an increase in the volume of daily waste generation that is not balanced by an adequate handling system. This study aims to optimize the waste management system in an integrated manner with an industrial engineering approach, especially through the application of the Lean Waste Management concept, redesigning facilities and logistics, and strengthening community participation based on Human-Centered Design (HCD). A qualitative method with a case study approach was used, with data triangulation techniques in the form of in-depth interviews, direct observation, and document analysis. The results of the study showed that 75% of households did not sort their waste, only 2 out of 6 TPSTs were active, and the TPA capacity had exceeded its limit since 2022. The efficiency of the transportation system is also low due to suboptimal routes and frequencies. This study offers solutions based on technology integration, facility redesign, logistics optimization, and community empowerment. With a systemic approach based on industrial engineering, an efficient and sustainable waste management model can be applied, not only in Kudus, but also in other areas with similar challenges.